2021
DOI: 10.1186/s12889-021-12020-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and levels of cervical Cancer screening uptake among women of reproductive age in South Africa: evidence from South Africa Demographic and health survey data, 2016

Abstract: Background Cervical cancer (CC) is the cancer with the most incidents and the leading cause of cancer mortality among women in South Africa. CC screening is one of the most cost-effective control approaches for the disease burden. This study assessed the determinants and individual-level indicators of cervical cancer screening uptake among women of reproductive age in South Africa. Methods We analyzed data from the 2016 South Africa Demographic Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 64 publications
5
31
1
Order By: Relevance
“…The study found that having an average or an above-average monthly income was associated with an increased likelihood of engaging in CCS than having a below-average income. This finding was reported in a South African study involving a secondary data analysis of the Demographic and Health Survey data [ 29 ]. The National Health Insurance Scheme in Ghana presently does not cover cervical cancer screening.…”
Section: Discussionsupporting
confidence: 74%
“…The study found that having an average or an above-average monthly income was associated with an increased likelihood of engaging in CCS than having a below-average income. This finding was reported in a South African study involving a secondary data analysis of the Demographic and Health Survey data [ 29 ]. The National Health Insurance Scheme in Ghana presently does not cover cervical cancer screening.…”
Section: Discussionsupporting
confidence: 74%
“…Evidence supports the nding that inequalities in these underserved cervical pre-cancer screening countries favoured women who were older, resided in urban areas, were more educated and in the highest wealth quintile than younger women, who lived in rural areas, were uneducated and in the lowest wealth quintile [9,17,18]. Studies conducted in Ethiopia, Rwanda, Tanzania, Zambia, and Zimbabwe, also support this nding [10,27,28,12,29,11,12,13,14,15].…”
Section: Discussionmentioning
confidence: 60%
“…Studies show that residence, geography, education, wealth, age, health insurance status, and the capacity of health systems in uence access to cervical pre-cancer screening. Other factors include, a history of multiple sexual partners, HIV-positive status and women's social interactions [9,10,11,12,13,14,15,16,17,18]. These studies showed that women who were older, resided in urban areas, and were more educated and wealthier were screened more often than younger, rural residents, uneducated, and poor women, with a few exceptions [9,19,20,21,22].…”
mentioning
confidence: 99%
“…This is similar to findings from Ethiopia, 8 , 9 , 14 , 16 and South Africa. 23 This is due to the effect of HIV on the immune system. Participants who had multiple sexual partners were more likely to have a positive VIA test.…”
Section: Discussionmentioning
confidence: 99%